Facile preparation of functional and hybrid coatings by precipitations of polypyrrole and lysozyme via co‐assembly process. Issue 37 (1st May 2021) - Zhou, Xing; Song, Renfang; Wang, Dong; Fang, Changqing; Song, Yonghua; Yu, Ruien; Wang, Qiang; Deng, Jingrui
Abstract: The integration of biological matters and functional polymers to generate novel hybrids with multi‐functional properties has attracted an increasing attention in organic/organic systems, possessing a great promise for sensor, medical, and materials science applications. In this work, a facile co‐precipitation method was developed to prepare conductive composite via a co‐assembly process with one‐step. Lysozyme was employed as an assembly template, and the pyrrole monomers were polymerized and aggregated with the lysozyme nanoparticles via oxide polymerization, forming a hybrid and functional coating with significant conductivity of ca. 6.7 × 10 −5 S. The structure and morphology of the hybrid is performed by X‐ray photoelectron spectroscopy, Fourier transform infrared spectrometer, transmission electron microscopy, field emission scanning electron microscope, and laser scanning confocal microscope, and so on. The results showed that the coating was composed of homogenously and densely hybrid nanoparticles with the diameter of ca. 250 nm, possessing a certain degree of bio‐adhesion from the lysozyme precipitations according to the 3 M peeling test. In addition, the composite performed good infrared radiation shielding property when it was coated onto normal gauze. It suggests that the composite consisting of lysozyme and polypyrrole precipitations in nanoscale may possess significantly potential applications as conductive and shielding materials. Abstract : A co‐assembly and deposition process for preparation of functional hybrids in nanoscale.